2019
DOI: 10.2478/cqpi-2019-0051
|View full text |Cite
|
Sign up to set email alerts
|

Quality Improvement of a Safety Valve with the Use of Numerical and Experimental Studies

Abstract: This article presents results of numerical modelling, simulation and test bench experiments of a hydraulic direct-acting relief valve was used as a safety valve. The analyzed safety valve was placed in a system consisting of a fixed-speed pump, a control valve, a hydraulic cylinder as an actuator and a second pressure valve in the load line used as a payload generator for the cylinder. In the first step mathematical model of the system was formulated in the form of a system of ordinary differential equations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Improving the production process should constantly focus on monitoring and reducing the variation of product characteristics and production process parameters [7]. Managers' task is to analyze variation using appropriate means to discover the message that variation communicates to us about how to improve the process [8,9]. Dr Deming, the quality guru, once observed that "virtually uniform product can be achieved only through the careful study of variation in the process and action by management to reduce or eliminate that variation" [1].…”
Section: Introductionmentioning
confidence: 99%
“…Improving the production process should constantly focus on monitoring and reducing the variation of product characteristics and production process parameters [7]. Managers' task is to analyze variation using appropriate means to discover the message that variation communicates to us about how to improve the process [8,9]. Dr Deming, the quality guru, once observed that "virtually uniform product can be achieved only through the careful study of variation in the process and action by management to reduce or eliminate that variation" [1].…”
Section: Introductionmentioning
confidence: 99%